THE EFFECT OF CALSITE CONSENTRATION ON THE SURFAKTANT AND NANO-PARTICLE INJECTION FOR ENHANCED OIL RECOVERY - Muhammad, Amrupranadi
The calcite content (CaCO3) is a mineral filler in rocks that contains two types of ions, namely calcium (Ca2+) and carbonate (CO32-). Each rock has varying surface hardness levels, one of which is the level of hardness on the calcite surface. Based on research, increasing the hardness of calcite in air can increase the repulsive force between calcite grains, which can affect the wettability of the rock surface. The uneven surface of the calcite surface can cause the rock to be oil-wet so that oil tends to remain attached to the surface. The oil-wet condition of the rock will affect changes in oil from the rock, resulting in a decrease in oil production in a reservoir. So, an oil recovery method is needed. In this research, a flood surfactant scheme was used with the addition of nanomaterial. With the presence of nonmaterial, it can change the wettability of a rock, increase the mobility of oil droplets, and reduce wettability. This research focuses on the effect of calcite on surfactant and nanoparticle injection, however, it is necessary to make synthetic cores with different calcite contents, namely 5, 10, and 15% wt. In this experiment, wettability measurements were conducted by contact angle measurements were carried out on each synthetic core by varying the conditions used, namely surfactant, nanoparticles, and brine. IFT testing was carried out at several surfactant solution concentrations, and the most effective results were at a concentration of 1.25 %wt, while the contact angle test results showed the smallest contact angle value at 15 %wt calcite content using surfactant A-127 + TiO2 500 ppm of 7.06°. In terms of increasing the recovery factor, it was found that calcite was 5 %wt with the use of waterflood at 29.34%, and if using surfactant flooding, it was 57.79%.